Deciphering perovskite decomposition in a humid atmosphere with TOF-GISANS. (November 2022) - Urwick, Adam N.; Bastianini, Francesco; Pérez, Gabriel E.; Dunbar, Alan
Abstract: Doping or alloying of the cations on the A-site and halides on the X site of ABX3 perovskites has been demonstrated as a successful technique for improving moisture stability of perovskite films for optoelectronic applications. Despite structural and electrical stability improvements, these films still undergo moisture induced degradation to Lead Iodide and other photo-inactive phases, reducing device lifetime and performance. Understanding of their moisture induced degradation has been limited by the contrast mechanisms and sensitivity of optical and x-ray scattering techniques. Time-of-Flight Grazing Incidence Small Angle Neutron Scattering (TOF-GISANS) presents itself as a powerful alternative capable of identifying low atomic weight phases and offering depth resolution. Herein we use TOF-GISANS to begin to uncover moisture induced degradation pathways in various mixed perovskite systems fabricated under ambient conditions and exposed to 90% rH in the dark for up to 12 h, showing poor stoichiometric homogeneity through the bulk of the film and facile formation of deuterated by-products at ambient temperatures. We find evidence indicative of formation of PbI2, and PbBr2 from peaks apparent in scattering from the surface of MAPbI3, FA 0.83 MA 0.17 Pb( I 0.83 Br 0.17 )3, and FA 0.83 Cs 0.17 Pb( I 0.83 Br 0.17 )3 thin films, with degradation less pronounced in the latter films containing Cs. Deuterated by-products form readily, resulting in decreasing average particle size as perovskite crystals swell and fragment from the grain periphery inwards. Cs 0.05 (FA 0.83 MA 0.17 ) 0.95 Pb( I 0.84 Br 0.16 ) 3 shows impressive phase resilience compared to the other mixtures, with minimal segregation to other phases observed in vertical cuts through the 2D scattering image, though still exhibits deleterious morphological degradation. TOF-GISANS is demonstrated as a powerful tool for characterisation of these materials, with significant potential for future investigations into phase changes in thin films.